Assistance in making ecobricks from inorganic waste: Improving motor skills and environmental awareness of autistic students - Muhammad Shodiq Ash Sidqi; Aulia Icha Saputri; Ardelia Salsabila Rahman; Weandy Putri Setya Wardana; N. Nurlaila; Dyah Worowirastri Ekowati; Minatun Nadlifah; Arina Restian; Erna Yayuk (Universitas Muhammadiyah Malang, 2024)
SD Muhammadiyah 9 Malang with the highest number of students with 24 classes produces plastic waste ± 0.5 kg per class. On average, every day produces ± 12 kilograms of unused plastic waste. Therefore, this service activity aimed to assist in making Ecobrick from inorganic waste: improving motor skills and environmental awareness of autistic students of SD Muhammadiyah 9 Malang. The methods used in this community service activity are potential problems, data collection, program planning, program concept preparation, creative concept creation related to the fine motor skills of autistic students, program implementation, program monitoring, and mentoring. The results of this service in the form of mentoring show an increase in motor skills in autistic students. Other results are in the form of Ecobrick products from inorganic materials in the form of pencil holders and shelves produced by autistic students. In the future, it is necessary to follow up to assist teachers accompanying autistic students in improving the quality of learning in the classroom.